Rethinking coastal cliff protection zones for landscape planning. What limits are enough? - Pena, S.B. (2021)
The coastal ecosystems are a key subject of contemporary research concerning coastline position changes, climate change effects, hazard assessment, and ecosystem services. The population density in the coastal areas accelerates the natural morphogenetic processes of these ecosystems. The land-use planning strategies can have a vital role in achieving coastal ecosystem stability and providing resilience to risks. This study’s primary goal was to compare and evaluate different methodologies of mapping the protection area near the cliff crests designated by Coastal Protection Zones (CPZ). It was also proposed an alternative model (CPZ model). It was expected to contribute to the discussion of the best land use in these areas. The work was applied at a local scale in Lourinh˜a Municipality and at a national level (Portugal). The local scale results showed that the CPZ model would protect an area with a width between 96 and 327 m from the cliff crest. In contrast, the 2012 Portuguese legal framework application only covers a width between two and 9 m. The land-use planning of these zones must be carefully planned, and soil sealing must not be encouraged. In Portugal, the built-up areas stay between 1.2% and 14% of the different CPZ mapped